Colonial and global interfacing : imperial hegemonies and democratizing resistances - Backhaus, Gary, 1953-; Murungi, John, 1943- (Cambridge Scholars Publ, 2007)
How space is owned through practices of domination that emerged through colonialism and have been sustained through capitalist social relations in a 'post-colonial' context. How Imperial power created, in Foucault's words, a 'boomerang effect' whereby the techniques developed to control and subjugate colonial subjects worked Other such efficiency that they were imported back into Western societies to create new orders of control. How while new social movements such as the Zapatistas have remapped the rural and developed new ways to challenge and transform politics, Western societies have sou.